Pulmonary Limitations in Heart Failure - Cundrle, Ivan (Clin Chest Med, 2019)
Ultimately in the pathogenesis of heart failure, the disease becomes a systemic illness with a marked impact on the respiratory system. This creates a significant codependence between organ systems that is accentuated as the disease progresses and is further enhanced during exercise where the respiratory system becomes a major contributor to exertional symptoms and an important marker to track disease severity and prognosis.